The "Coutumes de Beauvaisis" of Philippe de Beaumanoir - de Beaumanoir, Philippe (The Middle Ages Series, 2015)
F. R. P. Akehurst provides the first English translation of the complete text of Coutumes, the customary law of Clermont in the Beauvais region as it was practiced and understood in the late thirteenth century. The Coutumes de Beauvaisis provides a unique perspective on thirteenth-century civil and criminal trials